Hull Formula and Standard of Compensation for Expropriation in Postcolonial States - M. Ya’kub Aiyub Kadir (Universitas Syiah Kuala, 2017)
ABSTRACT: The contentious issue dealt with economic sovereignty for host states after decolonisa-tion process is foreign investment protection from expropriation by newly independent states. Hull formula has been widely used as an international law standard for compen-sation of expropriation. However, this standard has perceived as an unfair treatment from the former coloniser to its former colony. Even there has been an assumption that the existence of this standard is merely to protect and to maintain the economic dominance of developed states and their multinational companies in the Third World. This issue will be viewed through critical legal studies methodology, to assess the extent to which the ‘hull formula’ standard compatible to current need of postcolonial states. It would contribute to conceptual understanding and to attempt to reformulate the international standard of expropriation based on justice and fairness in postcolonial context. Hull Formula dan Standar Kompensasi dari Expropiasi di Negara-Negara Poskolonial ABSTRAK: Setelah progam dekolonisasi negara-negara jajahan, salah satu isu yang mencuat dalam hukum internasional adalah perlindungan investasi asing dari nasionalisasi negera negara baru merdeka. Dalam hal ini hull formula yang mulanya didesain oleh negara Amerika terhadap Mexico, digunakan sebagai standar kompensasi dari nasionalisasi. Dari perspektif negara negara poskolonial standar ini dianggap tidak adil, bahkan standar ini digunakan hanya untuk memperkuat dominasi negara negara penjajah di bekas jajahannya. Dengan menggunakan metodologi kajian hukum kritis, tulisan ini ingin mengkaji sejauhmana relevansi hull formula untuk diterapkan dalam konteks negara-negara poskolonial. Tulisan ini diharapkan dapat berkontribusi untuk pemahaman konsep tentang standar kompensasi terhadap nasionalisasi di negara negara poskolonial, dan dapat membuka wacana merumuskan kembali standar secara lebih fair dan adil dari perspektif negara postkolonial.